Answer: To find the inverse of the function, we need to make x as a function of y and at the final step make a switch between x and y (i.e. make x as y and y as x)
y = x² + 4x + 4 ⇒⇒⇒ factor the quadratic equation
y = (x+2)(x+2)
y = (x+2)² ⇒⇒⇒ take the square root to both sides
√y = x+2
x = √y - 2 ⇒⇒⇒ x becomes a function of y
final step:
∴ y = √x - 2 ⇒⇒⇒ the inverse of the given function
So, as a conclusion:
f(x) = y = x² + 4x + 4 ⇒⇒⇒ the given function
f⁻¹(x) = y = √x - 2 ⇒⇒⇒ the inverse of the given function
Answer:
12 and 24
Step-by-step explanation:
2 numbers, x in this case, with one being twice the other, one of them will be 2x, equals 36. Your equation would look like this: 2x+x=36. Simplify it to get 3x=36, divide the 3 and you get 12. 12 will be your small number then multiply by 2 to get your large one, 24.
Answer:
The correct answer is : DCQ ( angle) = DCE (angle)
Answer:
V=25
Step-by-step explanation:
Solve for
v
v
by simplifying both sides of the equation, then isolating the variable.
v
=
25
I'm not 100 percent sure I think d